HUBUNGAN KEAKTIFAN DALAM HIMA PRODI PPKN DENGAN INDEKS PRESTASI MAHASISWA PPKN UNIVERSITAS PGRI ADI BUANA SURABAYA - Suhartono, Suhartono (Buana Pendidikan, 2018)
This research was motivated by a student organization requires students to be active and independent role in running the holding organization. Students are expected to be able to contribute through his thinking in a student organization. The problem of this research is "How does the activity of the HIMA Education Program PPKn and there a relationship activeness of students in HIMA Education Program PPKn with achievement index of PPKn students on campus UNIPA Surabaya ".The goal is to determine the activity of the HIMA Education Program PPKn students and to determine the relationship of the activity of the HIMA Education Program PPKn student with student achievement index PPKn on campus UNIPA Surabaya. Activeness in this research is the students who are active as a board and as a member of HIMA PPKn UNIPA Surabaya. Achievement index in this research is the unit of ultimate value that describes the quality of teaching and learning process of each semester. In this study to measure the activity of students and grade is done by using questionnaires and documentation. Analyzed Data Technique using product moment correlation, the sample in this study consisted of 95 PPKn students UNIPA Surabaya year period 2015, 2016 , 2017. The data were obtained by questionnaire and documentation which there is a student IPK. Based on data analysis that has been done to produce a correlation coefficient -0,292 to 0,004 significant, because the significance < 0.05 then Ho is rejected and Ha accepted. This means that there is a significant correlation between the activity of the HIMA Education Program PPKn with achievement index of PPKn students in UNIPA Surabaya.